Bacteriological Spectrum of Different Infections and their Antibiogram at NICVD, Dhaka - Shahidullah, MS; Yusuf, MA; Khatun, Z; Ara, UKMN; Aziz, M; Rahman, MR; Hafiz, F (Cardiovascular Journal, 2014)
Background: One of the major causes of death in the current era is the infectious diseases. Aerobic bacteria are one of the most commonly isolated organisms from hospitalised patients. Objectives: The aim of the present study was to observe the infections caused by aerobic bacteria and their antibiotics susceptibility pattern. Methods: This retrospective study was carried out in the National Institute of Cardiovascular Diseases (NICVD) from January 2012 to December 2012 for a period of one year. Patients who were admitted in medical wards and medical ICU suffering from different infections were undertaken for this study. Proper thoroughly clinical examination, routine and specific investigations were done in each case. Microbiological samplings were tried on day 1, after completion of antibiotic therapy or in between as required. Aerobic bacterial culture and sensitivity tests were done according to clinical laboratory standard institute (CLSI) standard. Result: A total of 660 samples were studied of which male (70.0%) were predominant than female (30.0%). The highest number of patients was in the age group of 30-60 years (54.0%) followed by 15-30 years (21.5%) and less than 15 years (13.0%). The mean age with standard deviation was 38.61±19.236 years. The most common isolated bacteria was Escherichia coli (40.1%) followed by Pseudomonas species (30.4%), coagulase negative Staphylococcus (19.0%) and coagulase positive Staphylococcus (5.9%); however, beta-haemolytic Streptococcus (4.2%) was detected. Urine culture has yielded Pseudomonas species (13.3%), E. coli (71.1%) and CNS (15.0%). From pus Pseudomonas species (37.3%) was isolated mostly which was 62 cases followed by E. coli (31.3%), CNS (19.3%) and CPS (7.2%). Pseudomonas species was resistant to penicillin, amoxycillin and vancomycin and ~50% resistant to cotrimoxazole, cefuroxim, ceftriaxone, piperacillin, azythromycin, cephalexin, netelmycin and pfloxacillin. Conclusion: In the conclusion, majority bacteria are resistant to commonly used antibiotics. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18353 Cardiovasc. j. 2014; 6(2): 127-132